2015
DOI: 10.5455/aim.2015.23.68-72
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Cytogenetic and Molecular Methods in Prenatal Diagnostics of Chromosomal Abnormalities

Abstract: Aim:The aim of prenatal diagnostics is to provide information of the genetic abnormalities of the fetus early enough for the termination of pregnancy to be possible. Chromosomal abnormalities can be detected in an unborn child through the use of cytogenetic, molecular- cytogenetic and molecular methods. In between them, central spot is still occupied by cytogenetic methods. In cases where use of such methods is not informative enough, one or more molecular cytogenetic methods can be used for further clarificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It has been well accepted that women over age 35 at delivery are at higher risk for giving birth to a child with DS. In fact, for a long time, advanced maternal age (AMA) has been considered as a sole indication for genetic amniocentesis for definitive prenatal diagnosis ( Bornstein et al, 2009 ; Stomornjak-Vukadin et al, 2015 ). In our study, the incidence of DS in women over age 34 was significantly higher than in other age groups ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well accepted that women over age 35 at delivery are at higher risk for giving birth to a child with DS. In fact, for a long time, advanced maternal age (AMA) has been considered as a sole indication for genetic amniocentesis for definitive prenatal diagnosis ( Bornstein et al, 2009 ; Stomornjak-Vukadin et al, 2015 ). In our study, the incidence of DS in women over age 34 was significantly higher than in other age groups ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…FISH is the most commonly used method to evaluate CIN in patient samples [ 127 , 132 , 133 , 134 ], and studies carried out with this technique in parallel with other findings have shown that increased CIN can positively or negatively impact treatment responses [ 6 , 135 ].…”
Section: The Role Of Cin In Anticancer Therapy Responsesmentioning
confidence: 99%
“…For instance aneuploidy in porcine embryos was investigated using threecolor fluorescent in situ hybridization (FISH) method using chromosome-specific DNA probes; it enabled the establishment of baseline frequencies of aneuploidy in embryos, spermatozoa and oocytes [22,23]. Another molecular cytogenetic technique, primed in situ DNA synthesis (PRINS), has been applied to pig's genome to visualize the interstitial telomeric signal in the genome.…”
Section: Cytogenetics and Domestic Animal Studiesmentioning
confidence: 99%